The readiness of Indonesian toward MOOC system - Kurniasari, Florentina; Jusuf, Eddy; Gunardi, Ardi (International Journal of Engineering and Technology, 2018)
Learning through digital environment has become both trend and necessities for today’s education. One of the latest virtual learning trends is the Massive Open Online Course (MOOC). MOOC is spotlighted internationally and locally. Not only the internationally well-known, MOOCs, such as Coursera, edX, and Future Learn, many countries, including Indonesia, are also building their own MOOCs. However, how could this MOOC mode suitable for Indonesian learning culture? How would MOOC fit the Indonesian act of National Education System? In attempt to answer the questions, content analysis method would be used within the research through primary and secondary resources in the domain of MOOCs to see whether MOOC is potentially implemented in Indonesia based on the readiness of Indonesian learners to conduct self-study in digital environment and analysis on the act of National Education System.